2017
DOI: 10.1002/lary.26790
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and survival outcomes of sinonasal verrucous carcinoma in the United States

Abstract: 4. Laryngoscope, 128:651-656, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…13,[33][34][35] Indeed, HNVC characteristically has a markedly limited propensity for regional or distant metastasis, and enlarged cervical lymph nodes on physical examination are almost always reactive in nature. 13,34,36,37 Metastatic spread of HNVC remains especially uncommon as evidenced by a review of 101 patients with oral cavity VC treated surgically that reported no cases with adverse pathological features such as perineural invasion (PNI) and lymphovascular invasion (LVI). 18 Survival is thus favorable; the 5-year OS in our cohort was 71% which aligns well with existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[33][34][35] Indeed, HNVC characteristically has a markedly limited propensity for regional or distant metastasis, and enlarged cervical lymph nodes on physical examination are almost always reactive in nature. 13,34,36,37 Metastatic spread of HNVC remains especially uncommon as evidenced by a review of 101 patients with oral cavity VC treated surgically that reported no cases with adverse pathological features such as perineural invasion (PNI) and lymphovascular invasion (LVI). 18 Survival is thus favorable; the 5-year OS in our cohort was 71% which aligns well with existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…The local confinement of HNVC and its relatively benign histopathologic features, such as minimal cytological atypia and an intact basement membrane contribute to its late or potentially absent metastatic potential 13,33‐35 . Indeed, HNVC characteristically has a markedly limited propensity for regional or distant metastasis, and enlarged cervical lymph nodes on physical examination are almost always reactive in nature 13,34,36,37 . Metastatic spread of HNVC remains especially uncommon as evidenced by a review of 101 patients with oral cavity VC treated surgically that reported no cases with adverse pathological features such as perineural invasion (PNI) and lymphovascular invasion (LVI) 18 .…”
Section: Discussionmentioning
confidence: 99%
“… 3 Other reported locations in the head and neck region affected by verrucous carcinoma are nasal cavity, paranasal sinuses, nasopharynx, oesophagus and temporal bone. 12 , 13 , 14 Verrucous carcinoma on the skin and mucosa of the anogenital region and extremities are described in the literature as well. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%